Self-assembled hybrid organic–MoS3-nanoparticle catalyst for light energy conversion. Issue 45 (16th November 2020) - Krieger, A.; Wagner, M.; Haschke, S.; Kröckel, C.; Bachmann, J.; Hauke, F.; Hirsch, A.; Gröhn, F.
Abstract : Towards new routes for solar energy conversion: a novel supramolecular catalyst active in aqueous solution consists of amorphous molybdenum sulfide nanoparticles created in a polymer template. Abstract : We present photocatalytically active, stable polymer–amorphous–MoS3 -nanoparticle hybrid structures in aqueous solution. Below 10 nm MoS3 particles in the polymer exhibit an up to 7.5-fold increased photocatalytic activity compared to the neat nanoparticles without any additional photosensitizer. Supramolecular interactions are key in directing the structure formation of the hybrid assembly. The hybrid structures bear potential as novel affordable photocatalysts for solar energy conversion.